(untitled) (Research, Society and Development, 2022)
This study aims to describe the extension activities carried out in a Basic Health Unit on topics related to mental health. This is an experience report of actions carried out in a Basic Health Unit on topics related to mental health, by academics and professors of the fourth semester of the nursing course at the Centro Universitário do Vale do Araguaia (UNIVAR). The activities, which were organized and carried out, were carried out from August to September 2022. Four conversation circle actions were carried out in a Basic Health Unit, addressing the themes; anxiety, depression, drug abuse prevention and suicide prevention. In order to carry out these actions, informative folders are created on the themes and dynamics of interaction. In total, around 103 individuals were assisted, including academics, professors, users and professionals of the health system. In this way, it is concluded that extension activities are presented as a potential strategy for the insertion of academics in the midst of Nursing praxis. The organization, planning and execution of the actions were carried out entirely by the academics with supervision and suggestions from the professors, it is worth adding that in view of the actions carried out by the academics, it was possible to perceive aggregation of skills in the curriculum and training of the same, such as: communication, manual dexterity, teamwork, proactivity, humanized bonding with the patient, organization and planning, clinical reasoning and decision-making capacity.